Semangat buluh dalam masyarakat Bidayuh sebagai idea penciptaan karya - Anyshya, Jusam (Universiti Malaysia Sarawak (UNIMAS), 2016)
The study Is part of research and courses GKV 3206 final year project out by final year student of the department of Visual Arts and Technology. The selected research focus on the spirit of Bidayuh bamboo as the creation of ideas. Study is intended to exemine in more detail about the culture and the Bidayuh community's dependence on the bamboo then translated in the works titled communities, where media use is using clay and metal. In this work study only focuses on bamboo spirit as the subject matter. Through this study, the researchers tried to analyze all the problems and conflicts that were felt throughout this study.